2013
DOI: 10.1073/pnas.1221637110
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-specific responses to sustained uniaxial stretching in focal adhesion growth and turnover

Abstract: Cells are mechanosensitive to extracellular matrix (ECM) deformation, which can be caused by muscle contraction or changes in hydrostatic pressure. Focal adhesions (FAs) mediate the linkage between the cell and the ECM and initiate mechanically stimulated signaling events. We developed a stretching apparatus in which cells grown on fibronectin-coated elastic substrates can be stretched and imaged live to study how FAs dynamically respond to ECM deformation. Human bone osteosarcoma epithelial cell line U2OS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 54 publications
8
75
0
Order By: Relevance
“…This is consistent with the observation that stretch induces disassembly of FAs oriented perpendicular to the strain vector and growth of FAs parallel to the strain (35). Such force-induced activation of oriented integrins could mediate direction-dependent mechanosensing that promotes cell polarization in response to stretch and/or blood flow in the vasculature.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the observation that stretch induces disassembly of FAs oriented perpendicular to the strain vector and growth of FAs parallel to the strain (35). Such force-induced activation of oriented integrins could mediate direction-dependent mechanosensing that promotes cell polarization in response to stretch and/or blood flow in the vasculature.…”
Section: Discussionsupporting
confidence: 90%
“…Sawada et al have demonstrated that stretch-mediated force extends Cas to open the substrate binding domain and permit Src-mediated phosphorylation (17). Chen et al have shown that activation of FAK in focal adhesions is induced by cellular stretching (54). We and others have shown that FAK activation is required for stiffness-sensitive cyclin D1 expression (6, 8, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation is in support of the theory of forcemediated FA dynamics 43 and is also consistent with results reported by others. 35 Given its unique capability for external stretch and subcellular live-cell imaging, our device provided a useful platform for studying mechanosensitive subcellular FA dynamics as a critical component of cellular mechanotransduction. …”
Section: A Force-mediated Focal Adhesion Dynamics Under Step-functiomentioning
confidence: 99%
“…Numerous cell stretching devices have been developed in previous studies and applied to explore cellular behaviors in response to controlled external stretch. 9,14,17,21,[33][34][35][36][37][38][39][40] However, many of these implementations have significant limitations. With the exception of several state-of-the-art devices, such as the commercial Flexcell systems, which rely heavily on sophisticated pneumatic control systems for regulating air pressure, the regulation on the dynamic stretch is not demonstrated for most vacuum-driven cell stretchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation